Synthesis Characterization and Anti Microbial Screening of some Schiffs Bases of 2 Methyl Benzimidazole Derivatives - N, Sanahanbi (International Journal of Pharmaceutical & Biological Archive, 2014)
Synthesis Characterization and Anti Microbial Screening of some Schiffs Bases of 2 Methyl Benzimidazole Derivatives